Línea de investigación: la sexualidad y la clínica (1998)
ABSTRACT: In this article a description of line of research: sexuality and the clinics is done. This line of research is carried out by the University Of Antioquia School Of Nursing. The sequence on the development of research project related with the clinics is shown taking into consideration a humanist, interinstitutional, and multidisciplinary approach. The object of sexuality is viewed as need within the mental health.